Life threatening water intoxication - Ahmed, Shahad W. (The Iraqi Journal of Veterinary Medicine, 2020)
Water intoxication is a fatal disorder associated with disturbance in brain function, known as hypo-osmolar syndrome which resulting from an excessive water intake, with dilutional hypernatremia leads to a potentially fatal outcome. A change in the electrolyte equilibrium such as this sudden drop in serum sodium level and then subsequent mortality. With hyponatremia, the plasma osmolality decreased leading to water movement into the brain according to the osmotic gradient, resulting in hyponatremic encephalopathy and cerebral oedema. Increased water intake such as in Psychogenic polydipsia is followed by urination of high amount of diluted urine (polyuria) which are the main initial symptoms of water intoxication with headache, blurred vision, nausea, tremor, and deterioration in psychosis. Other serious symptoms involve muscle spasms, Early detection of seizures and coma are more serious outcomes, Untreated cases may lead to death, Risk factor for water intoxication are Marathon runners, military population and athletes and due to this endurance events, these behaviors encouraging heavy sweating that result in heat exhaustion and consume large volumes of fluid, then hyponatremia developed as a result of excessive fluid substitution. Child abuse is other pediatric clinical cases reported with water intoxication. Psychogenic polydipsia which is psychiatric disorder with obsessive water drinking leading to a serious self-induced water intoxication (SIWI), water is normally metabolized and excreted by different means and it is mainly by kidneys in urine, evaporation through the skin, by respiratory system through the respired water vapor and little quantity of water was lost from the gastrointestinal tract (GI).The LD50 of water is > 90 ml/kg orally in rats. The current review illustrates the Life threatening effects of water when it is aggressively consumed.